Integration оf Foreign Educational Technologies іn the Content of Program of Pre-School Education in Ukraine - Nadiia Frolenkova (Vasyl Stefanyk Precarpathian National University, 2017)
Reveals the integration and implementation of foreign educational technologies in the content of educational programs of preschool education in Ukraine. The emphasis on the implementation of programs for the ideas of Waldorf education, Montessori programs, "SelfEsteem", "Step by Step", "Education for sustainable development for children of pre-school age". It is proved that the integration of foreign educational technologies in the process of optimizing the scientific and methodological support preschool education content Ukraine simulated based priority, primarily oriented humanistic, pedagogical ideas and technologies. Key words: educational technologies, integration, educational program, content of preschool education, children of pre-school age.